Stone-free Rate of Ultrasound-assisted and Fluoroscopy-guided Extracorporeal Shockwave Lithotripsy for Radiopaque Renal Stones - Khan, Muhammad Nawaz; Hassaan ul Hassan,; Haneef, Faisal; Jafri, Abbas; Saad, Hafiz Muhammad; Kumar, Sanjeet; Syed Rabiullah,; Gazder, Tanzeel (Indus Journal of Bioscience Research, 2024)
Background: Extracorporeal shock wave lithotripsy (ESWL) has been a widely accepted method for treating urinary stones since the early 1980s. ESWL is the preferred non-invasive treatment for renal stones that are smaller than 1.5 cm. Ultrasound and fluoroscopy are used during ESWL operations to visualize the fragmentation. Objective: To determine the Stone-free rate of ultrasound-assisted and fluoroscopy-guided extracorporeal shockwave lithotripsy for radiopaque renal stones. Methodology: A prospective cohort study was conducted at the Sindh Institute of Urology and Transplantation from 25th February to 25th August 2022, including 75 participants per group with renal stones <1.5 cm, radio-opaque kidney stones, and consented patients. Both groups were treated using identical lithotripters with ultrasound and fluoroscopy for stone localization. Post-lithotripsy, X-ray or ultrasound assessed stone clearance. Frequency and percentages were calculated for variables like age, gender, and stone-free rates. Mean values and deviations were computed. The Chi-Square test analysed categorical variables. Paired sample statistical analysis evaluated differences in stone size and clearance, with p-values <0.05 deemed statistically significant. Results: Within group A, 53 patients (70.7%) exhibited no stones, whereas in group B, 45 patients (60%) were devoid of stones. These findings suggest that group A surpassed group B in terms of achieving stone-free statuses. Conclusion: Our research findings indicate that ultrasound-assisted extracorporeal shockwave lithotripsy achieved a stone-free rate of 70.7%, surpassing the stone-free rate of 60% achieved by fluoroscopy-guided extracorporeal shockwave lithotripsy for radiopaque renal stones.